Carcinogênese quimicamente induzida por DMBA em glândulas salivares submandibulares de ratos (rattus norvegicus) - Mainenti, Pietro [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A carcinogênese consiste em um processo de alterações genéticas após contato celular com agentes físicos, químicos ou biológicos. Esta interação pode culminar em manifestações de fenótipos malignos celulares. No estudo experimental da carcinogênese em glândulas salivares animais, os autores são unânimes em apontar os hidrocarbonetos policíclicos aromáticos (HPA) como potentes agentes carcinogênicos. O 7,12 - dimetilbenzantraceno (DMBA), pertencente ao grupo dos HPA, é considerado o carcinógeno químico de eleição para a tumorigênese de glândulas salivares animais. Este trabalho visou o estudo de DMBA injetado em glândulas salivares submandibulares de ratos. Foram utilizados 28 ratos (Rattus norvegicus), com três meses de idade e peso aproximado de 300g. Os resultados revelaram, na 5ª semana, sete casos de sialadenite crônica. Na 10ª semana, um caso com atipia celular ductal, dois casos de carcinoma epidermóide e quatro de sialadenite crônica. Entre a 15ª e 20ª semanas, foram observados três casos de hiperemia, três casos de carcinoma epidermóide, um caso de sarcoma e sete casos de carcinossarcoma. A análise dos dados, em porcentagem, revelou: 3,6% de atipia celular, 3,6% de sarcoma, 10,7% de hiperemia, 17,9% de carcinoma epidermóide, 25% de carcinossarcoma e 39,4% de sialadenite crônica. Conclusão: Os dados obtidos permitiram o estudo da história natural da carcinogênese glandular por DMBA desde os processos inflamatórios iniciais até à formação de neoplasias mesenquimais, epiteliais e mistas.

The carcinogenesis consists in a process in which the direct contact between cells and some physical, chemical or biological agents results in cell malignization. In the scope of experimental salivary gland carcinogenesis there is a consensus in the use of polycyclic aromatic hydrocarbons (PAH) as carcinogens. The 7,12 - dimethylbenzanthracene (DMBA) is the most used PAH. This paper aims the investigations of the DMBA injected in rats submandibular glands. For this purpose, 28 rats (Rattus norvegicus), three months old (300 gr. weight, approximately) were used. The animals were divided into four groups of seven each. All animals were anesthetized and shaved in the neck. After antisepsis, one ventral neck incision, followed by dissection was performed in each animal. The left submandibular gland was injected with 0.1 ml of 2% DMBA in acetone. The skin was closed with 3-Ø silk suture. By the end of the 5th, 10th, 15th and 20th weeks the animals were sacrificed by lethal doses of anesthetics. The results in the 5th week presented seven cases of chronic sialadenitis. After 10 weeks one case of ductal cell atypia was evident, two cases of squamous cell carcinoma and four cases of chronic sialadenitis were also seen. Between the 15th and 20th weeks the cases were diagnosed as follows: three cases of hyperemia, three cases of squamous cell carcinoma, one case of sarcoma and seven cases of carcinosarcoma. The data analysis showed 3.6% of cellular atypia, 3.6% of sarcoma, 10.7% of hyperemia, 17.9% of squamous cell carcinoma, 25% of carcinosarcoma and 39.4% of chronic sialadenitis. Conclusion: the results allowed the investigation of the glandular carcinogenesis natural history after DMBA injection, from the beginning of inflammatory changes to the neoplastic manifestation of mesenquimal, epithelial and mixed tumours.
Keywords: Glandulas salivares; Tumores; Carcinogenese; Mucosa bucal; Carcinogenesis; Salivary gland